Attention Economy & Marketing Strategies in India (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Due to hectic working hours and rapidly expanding digital infrastructure and usage of information and technology tools, there is bombarding of information. Due flood of information the human attention has become scarce. The average time spend by an Indian on mobile is more than 4.5 hours and total screen time is as about 7 to 8 hrs. Especially after covid the screen time habit shows increasing trend. With heavy population of 140 crore and high screen time the marketers see huge opportunity to promote the product. But attentions of the viewers is the biggest problem for them. The current paper aims to study the attention economy in India and the various marketing strategies used by the marketer to capture and convert the captured attention into revenue. Different strategies like visual hooks, flash sales, AI tools and many more are used to increase the sales turnover by the marketers.